The Influence of Product Quality, Influencer Credibility and Online Customer Reviews on Purchase Decisions of Facetology Skincare Products (Study on Consumer Students of the University of Muhammadiyah Purwokerto) - Burhan Feisal Fajri; M. Agung Miftahuddin; Arini Hidayah; Meydy Fauziridwan (Indonesian Journal of Business Analytics, 2025)
This study aims to determine the influence of product quality, influencer credibility, and online customer reviews on the purchase decision of Facetology skincare products. The research population included students of the University of Muhammadiyah Purwokerto with a total of 113 respondents who were selected using the purposive sampling technique. This study uses a quantitative approach with multiple linear regression analysis through the SPSS version 23 program. Based on the results of the analysis, it is shown that product quality and online customer reviews have a positive and significant effect, but the credibility of influencers has a negative and insignificant effect on purchase decisions. These findings are expected to serve as a reference for local skincare industry players in formulating more effective and credible marketing strategies.